The inspection of education in Portugal - Lucas, Clara; Azevedo, José João (Avances en Supervisión Educativa, 2010)
In order to clarify the procedures of the Portuguese Inspectorate of Education (IGE), this paper begins with a brief exploration of the legal framework of the inspection of education, using a diachronic perspective. Then, some comments on the reconceptualization of the inspection action, highlighting the changes in IGE, are made, in an approach for monitoring and steering centered on production of relevant information about the quality of performance of schools.  We also present IGE's aims, its organization, and its current programmes and activities, with particular emphasis on the External Evaluation of Schools for the importance this evaluation programme nowadays has. Finally, a critical reflection is drawn on the role of the inspector, and his rigorous knowledge of school organizations, in order to be able to assess, encourage and recommend procedures.